GAMBARAN RITME SIRKADIAN NELAYAN DI TANJUNG EMAS SEMARANG - Evi Sondang Sidabutar; Bina Kurniawan; Baju Widjasena (Jurnal Kesehatan Masyarakat (Undip), 2015)
Naturally, our body is created to beactive during the day light and we need to rest at night. If the body's biological time does not work on normal hours, it will affect the body's circadian rhythm. The problem on the circadian rhythm could cause health problems, occupational safety, and social aspects. This study aims to determine the circadian rhythms of fishermen who work in Tanjung Emas Semarang. The method of this study is description observational study. The measurement of circadian rhythm used various tools, such as sphygmomanometer for blood pressure, digital thermometer for body temperature, digital sphygmomanometer for pulse and a questionnaire for sleep patterns. The measurement of risk factors of circadian rhythm disorders is also done by using various tools such as a multimeter to measure the noise, temperature and humidity of the environment and a questionnaire to determine the behavior of fishermen. The measurements were taken every two hours for 24 hours, either on land or sea while working.The results showed the risk factors of circadian rhythm disorders are noise, temperature and humidity of the working environment and sleep patterns.Blood pressure and body temperature of fishermen who do not regularly work at night are higher at work than at rest, but there is a difference on fisherman who regularly work at night. Blood pressure and body temperature of fishermen who regularly work at nights are lower while working than at rest. In general, the pulse of fishermen who work at night is higher during work than rest time. Blood pressure and temperature of fisherman who work at daylight and don’t sleep at the right tme are higher during work than rest time. Blood pressure and temperature of fishermen who work at daylight and sleep at the right time are lower during work than rest time. The pulse of fishermen who work at daylight and don’t sleep at the right time are lower during work than rest time. But the pulsa of fishermen who work at daylight and sleep at the right time are higher during work than rest time. On conclusion, sleep and awake’s rhythm od fishermen who work either daylight or night are not normal. Because of that, keeping a sleep pattern, noise, temperature and humadity control of workplace is a very important matter to be done.